Do High Salaries Ensure Job Satisfaction? : An Investigation on the Factors Affecting Job Satisfaction of Educators in Indonesia - Nuzulia, Siti; Saputra, Hijrah (Journal of Nonformal Education, 2022)
Job satisfaction is demonstrated to boost productivity. It is not easy, nevertheless, to create conditions to enhance job satisfaction. Objective workplace factors such as a big salary and a high-ranking position are insufficient to provide job satisfaction. Job satisfaction necessitates job characteristics that promote meaningful employment and also individuals’ potential to develop. This study aims to explore the factors that influence job satisfaction in educators. A total of 522 educators (i.e., teachers, lecturers, and trainers) participated in this study. The results of the research show salary had no impact on educators job satisfaction.  Jobs position has a positive effect on job satisfaction but is not greater than job characteristics, which include job authenticity, quality of work performed, meaningful feelings obtained through work, work that stimulates personal development, and work that recognizes one's accomplishments. This study provides helpful insights for organizations to identify the importance of job characteristics that contribute the most to educators job satisfaction.